Partnership and Service Operation Systems in Improving the Performance of Samsat Service Operations in West Java - Mukti Subagja (Ilomata International Journal of Social Science, 2022)
The government has regulated the pattern of identification and registration of motor vehicle ownership administration and the pattern of imposition of taxes, including compulsory donations of traffic accident funds through the One Roof Motor Vehicle Administration System, abbreviated as SAMSAT. The performance of service operations at the SAMSAT office in West Java Province has not reached the optimal stage. This is allegedly related to the implementation of service operations and partnership systems. Therefore, this study aims to examine the effect of partnerships and service operating systems on the operational performance of SAMSAT services in West Java. The research method used in this study is survey research. The unit of analysis is the SAMSAT office in West Java Province with an observation unit that is an apparatus from the SAMSAT office in West Java Province spread over 27 districts / cities. Based on a small population size, a census of the entire population is carried out. Causality analysis is used to determine the causal relationship between variables, using PLS. The results of the study show that partnerships and service operating systems have a significant effect on operating performance. System operating performance has a more dominant influence than partnerships in increasing SAMSAT operating performance. The results of this study have implications for the SAMSAT apparatus in West Java Province that efforts to develop operational performance of SAMSAT services can be done by prioritizing the development of service operating systems and supported by the development of closer partnerships with related parties.